Implications of Synkinesis in Unilateral Vocal Fold Paralysis. (December 2017) - Pei, Yu-Cheng; Chang, Wei-Han; Chuang, Hsiu-Feng; Chang, Chia-Fen; Fang, Tuan-Jen
Objectives: In patients with unilateral vocal fold paralysis (UVFP), laryngeal electromyography (LEMG) occasionally observes synkinesis in laryngeal muscles, a condition that could impair vocal fold mobility and voice control. This study aims to evaluate the impact of synkinesis on UVFP patients. Study Design: A retrospective case-control study. Setting: Medical center. Subjects and Methods: Patients with UVFP onset >6 months were recruited (N = 104). The outcome measurements included LEMG, quantitative LEMG analysis of thyroarytenoid–lateral cricoarytenoid (TA-LCA) muscle complex, glottal gap measured by videolaryngostroboscopy, voice-related quality of life, and voice acoustic analysis. Results: According to the LEMG analysis, 8 patients (8%) had synkinesis, and 96 (92%) did not. In the synkinesis group, TA-LCA turn frequency in the lesioned side was comparable to that in the healthy side ( P = .52). Patients in the synkinesis group had higher TA-LCA turn frequency ( P = .001), higher probability of cricothyroid muscle dysfunction ( P = .04), and better voice-related quality of life ( P = .01) but objective voice outcomes comparable to those in the nonsynkinesis group. Conclusions: Patients with synkinesis will have near-complete restoration in TA-LCA turn frequency but still experience voice impairment, a finding that is compatible with the mechanism of aberrant reinnervation. However, patients with synkinesis have better disease-related quality of life than do those without synkinesis.